South Africa’s earliest giant: The systematics and palaeobiology of a new species of sauropodomorph - Moopen, Atashni (University of the Witwatersrand, Johannesburg, 2023)
Sauropodomorph dinosaurs are characterized by their gigantic body size and quadrupedal postures, but they evolved from small, bipedal ancestors. Transitional non sauropodan sauropodomorphs from the Norian are key to understanding this evolutionary transition. A new Norian sauropodomorph (BP/1/8469) discovered in 2018 in the lower Elliot Formation of Qhemegha, Eastern Cape consists of a well-preserved, well-represented associated postcranial skeleton of a relatively large individual. This specimen provides novel information about the Norian transition in sauropodomorph body plan. This study presents the results of BP/1/8469, using comparative anatomical study, quantitative body mass and postural estimation, osteohistological enquiry, and phylogenetic systematics assessment. BP/1/8469 is a 1.8 to 3.1 metric tonne, facultative quadrupedal sauropodomorph. It was an adult that displays rapid, interrupted growth, similar to other sauropodiforms. Phylogenetic analysis of BP/1/8469 highlights incongruencies in sauropodomorph character datasets, flags considerable homoplasy in sauropodomorph evolution, and underscores the need for accurate homology statements.
A research report submitted in fulfillment of the requirements for the Master of Science in Palaeontology, In the Faculty of Engineering and the Built Environment, Faculty of Science,, University of the Witwatersrand, Johannesburg, 2023
Keywords: UCTD; Elliot Formation; Sauropodomorph; quadrupedalism; osteohistology; Fossilized Birth-Death models; SDG-4: Quality education; SDG-9: Industry, innovation and infrastructure